1996
DOI: 10.1080/00224545.1996.9713993
|View full text |Cite
|
Sign up to set email alerts
|

First Names as Identity Stereotypes

Abstract: Four hundred eight high school and college students in Israel were presented with a sample of 12 typical first names divided on an a priori basis into 2 categoriesIsraeli and Jewish-with the former subdivided into recently coined and biblical names and the latter into names of general use and names of special significance to the diaspora. The names were to be rated on a 12-scale semantic differential and on 3 additional scales (Close to me-far from me, Israeli-Jewish, Israeli non-Jewish). Analysis indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…As a result, individuals may fail to recognize the subtle and persistent effects their names have on the way that others perceive them in various social or professional situations. A number of studies have investigated how names influence different forms of attribution such as physical attractiveness, intelligence, achievement, ethnicity, collective inclusion or exclusion, popularity, and competence (Daniel & Daniel, 1998;Dinur et al, 1996;Erwin, 1993;Hargreaves et al, 1983;Hassebrauck, 1988;Young et al, 1993). These studies suggest that first names elicit such distinct opinions about the bearer of the name that they become the primary basis for stereotyping.…”
Section: The Significance Of Namesmentioning
confidence: 99%
“…As a result, individuals may fail to recognize the subtle and persistent effects their names have on the way that others perceive them in various social or professional situations. A number of studies have investigated how names influence different forms of attribution such as physical attractiveness, intelligence, achievement, ethnicity, collective inclusion or exclusion, popularity, and competence (Daniel & Daniel, 1998;Dinur et al, 1996;Erwin, 1993;Hargreaves et al, 1983;Hassebrauck, 1988;Young et al, 1993). These studies suggest that first names elicit such distinct opinions about the bearer of the name that they become the primary basis for stereotyping.…”
Section: The Significance Of Namesmentioning
confidence: 99%
“…however, little is known about the effect of names from different social, cultural, or linguistic groups. in the only study of this question, dinur, Beit-hallahmi, and hofman (1996) found that although israeli students did not differ in their ratings of names that were traditionally israeli, those who were more religious rated traditionally Jewish names more positively than those who were less religious. The authors state that these results support Tajfel's social identity theory, according to which people form their identity, at least in part, from groups to which they feel a sense of belonging.…”
mentioning
confidence: 82%
“…According to Dinur, Beit-Hallahmi and Hofman (1996), the first name given to any person is a representation of their identity. While family names (last names) stay consistent from generation to generation, the first name tends to change given the time period and trends within that given culture.…”
Section: Student Identification Biasmentioning
confidence: 99%